NONLOCAL PROBLEM FOR A MIXED TYPE DIFFERENTIAL EQUATION IN RECTANGULAR DOMAIN - Yuldashev, T.K. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
In the article the questions of solvability and construction of the solution of nonlocal mixed value problem for a homogeneous mixed type differential equation are considered. The spectral method based on the separation of variables is used. A criterion for a single-valued solvability of the considered problem is installed. Under this criterion the single-valued solvability of the problem is proved. The existence of problem solutions in the case of uniqueness failure is studied, also.
Keywords: mixed value problem, mixed type differential equation, integral condition, one valued solvability